The cathedrals of Pisa, Siena and Florence - Matracchi, Pietro, author.
1 online resource (xv, 299 pages)
Keywords: "The construction techniques and concepts of the cathedrals of Pisa, Siena and Florence are examined in detail, based on new data and using a methodological architectural diagnostics approach. New detailed surveys, carried out using often advanced tools, together with direct and in-depth inspections to examine all parts of the buildings, have enabled us to identify the building phases and the different construction techniques used over time. The information thereby acquired also formed the basis for a new interpretation of the archival documents. Accordingly, the problems encountered and the solutions adopted in the three cathedrals have been understood: in Pisa the construction of the elliptical dome above the rectangular crossing consisting of six thin pillars below; in Siena the design changes from the first system in the 13th century to the 'Duomo Nuovo', and the structural adaptations following earthquakes; the specific construction solutions adopted in Florence during the instability encountered in the construction of the large vaults of the basilican body. The comparison of the three buildings in terms of architectural and construction solutions also revealed unexpected relationships between the construction events of Siena's Duomo Nuovo and the solutions then used in the large basilican body of Santa Maria del Fiore. The methodology employed has led to an understanding of the actual structure of the three cathedrals, an essential basis for a correct evaluation of the state of conservation of the churches for any restoration work. The book is aimed at scholars of architecture and ancient building structures, graduate and postgraduate students, and architects and engineers who plan architectural conservation and strengthening works for historical buildings"--